2016
DOI: 10.1186/s13256-016-0925-4
|View full text |Cite
|
Sign up to set email alerts
|

Visceral symptoms as a key diagnostic sign for the early infantile form of Niemann–Pick disease type C in a Russian patient: a case report

Abstract: BackgroundNiemann–Pick disease type C is a rare metabolic disease characterized by progressive neurological deterioration with childhood onset, and often results in premature mortality. Niemann–Pick disease type C has an extremely heterogeneous clinical presentation with a wide range of visceral and neurological signs and symptoms that are not specific to the disease, and which progress over varied periods of time. The incidence and epidemiology of Niemann–Pick disease type C in Russia have not been characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Although the onset and progression in this case were similar to that seen in the severe infantile form, the disease form was more compatible with the late infantile form due to the age at death and the patient's disturbed eye movement and acquired ambulation . A recently developed drug miglustat has proven to be effective for similar infantile forms of NPC that involve disturbed ocular movement and ambulation …”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Although the onset and progression in this case were similar to that seen in the severe infantile form, the disease form was more compatible with the late infantile form due to the age at death and the patient's disturbed eye movement and acquired ambulation . A recently developed drug miglustat has proven to be effective for similar infantile forms of NPC that involve disturbed ocular movement and ambulation …”
Section: Discussionmentioning
confidence: 52%
“…1,2 A recently developed drug miglustat has proven to be effective for similar infantile forms of NPC that involve disturbed ocular movement and ambulation. 3 Our patient harbored compound heterozygous mutations of the NPC1 gene, with the missense mutation T2108C (F703S) and the nonsense mutation C2348G (S813X), neither of which have been previously reported. The single nucleotide polymorphism (SNP) database includes a base change that causes an F703I amino acid change, but this variant has not been reported to be disease-causing.…”
Section: Discussionmentioning
confidence: 63%
“…In a recent epidemiologic study of 53 patients with NPC in the United Kingdom, 17 (32%) had a systemic presentation [24]. Systemic manifestations include neonatal cholestatic jaundice, sometimes progressing to fulminant liver failure, transient jaundice in the newborn period, isolated hepatomegaly or splenomegaly or both, and/or evidence of hypersplenism (decreased blood counts such as thrombocytopenia, leukopenia, or anemia related to enlarged spleen size) [1, 14, 24, 32, 33]. NPC should be strongly suspected in the neonate with cholestasis [34] and is one of several inherited metabolic disorders to be a recognized cause of fatal acute liver failure in the newborn or young child [35].…”
Section: Introductionmentioning
confidence: 99%
“…HPβCD is the only drug that has been proven to ameliorate neurodegeneration and prolong the life span of NPC1 mice ( Liu et al 2009 ) and thus far has shown promising results in a small cohort of older NPC1 patients (World 2017 posters). Diagnosis of NPC1 in infants before development of neurologic disease is uncommon ( Degtyareva et al 2016 ). A literature review identified only two prior cases of patients diagnosed with NPC in infancy who started miglustat therapy upon diagnosis.…”
Section: Variant Interpretationmentioning
confidence: 99%